Tres hermanas hispano-judías judaizantes condenadas por la Inquisicion. Sus personalidades - Susana M. Likerman de Portnoy (Estudios de Historia de España, 2017)
Reading the court records of crypto Conversos by the Inquisition of Castilla, allows us to understand the psychological characteristics of the Converso personalities.Our study is centered on three sisters that were judged, two of them found guilty and executed; and the other sentenced to be whipped and expatriated. It is important to study these women in order to develop a more general interpolation for micro-history.